Utility of interim and end-of-treatment [18F]-fluorodeoxyglucose positron emission tomography–computed tomography in frontline therapy of patients with diffuse large B-cell lymphoma. Issue 9 (2nd September 2015) - Huntington, Scott F.; Nasta, Sunita D.; Schuster, Stephen J.; Doshi, Jalpa A.; Svoboda, Jakub
Abstract : [ 18 F]-fluorodeoxyglucose positron emission tomography–computed tomography (PET/CT) is part of standard pretreatment staging and post-treatment assessment in patients undergoing first-line therapy for diffuse large B-cell lymphoma (DLBCL). While many providers obtain interim PET/CT (I-PET) for DLBCL, the clinical utility of these scans is unclear. We conducted a retrospective study of patients with DLBCL undergoing I-PET during first-line therapy ( n = 94). The majority (61%) of patients had at least one negative I-PET and all patients with negative I-PET remained in remission at the end of treatment. I-PET was strongly associated with progression-free survival and remained independent on multivariable modeling (non-complete remission [CR]:CR I-PET, hazard ratio 2.7, p = 0.01). All patients with negative I-PET were in remission at the end of frontline therapy, and end-of-treatment PET/CT offered little clinical utility in this subset. Therefore, I-PET may offer an approach of early clinical predication and obviate the need for end-of-treatment imaging in the majority of patients with DLBCL.